2013
DOI: 10.1302/2046-3758.26.2000165
|View full text |Cite
|
Sign up to set email alerts
|

Existence of mesenchymal stem cells in sites of atrophic nonunion

Abstract: ObjectivesNonunion is one of the most troublesome complications to treat in orthopaedics. Former authors believed that atrophic nonunion occurred as a result of lack of mesenchymal stem cells (MSCs). We evaluated the number and viability of MSCs in site of atrophic nonunion compared with those in iliac crest.MethodsWe enrolled five patients with neglected atrophic nonunions of long bones confirmed by clinical examinations and plain radiographs into this study. As much as 10 ml bone marrow aspirate was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…In our previous study, we revealed the existence of mesenchymal stem cells in atrophic non-union fracture site [8]. However, in our, we did not evaluate the osteogenic potency of those cells in the study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In our previous study, we revealed the existence of mesenchymal stem cells in atrophic non-union fracture site [8]. However, in our, we did not evaluate the osteogenic potency of those cells in the study.…”
Section: Discussionmentioning
confidence: 77%
“…In our previous study, we found that MSCs exist in the site of atrophic non-union fracture [8]. However, whether they are capable to differentiate into osteoblast was not evaluated.…”
Section: Introductionmentioning
confidence: 97%
“…8,[23][24][25] The biological inactivity of atrophic bone ends has been questioned by authors in recent literature. 24,[26][27][28][29] Brownlow et al 26 and Reed et al 27 showed that the vascularity of atrophic nonunions is comparable to that seen in fresh fractures and hypertrophic nonunions. Ismail et al 29 showed that mesenchymal stem cells were present at the site of atrophic nonunions at similar number and viability than those isolated from the iliac crest.…”
Section: Discussionmentioning
confidence: 98%
“…24,[26][27][28][29] Brownlow et al 26 and Reed et al 27 showed that the vascularity of atrophic nonunions is comparable to that seen in fresh fractures and hypertrophic nonunions. Ismail et al 29 showed that mesenchymal stem cells were present at the site of atrophic nonunions at similar number and viability than those isolated from the iliac crest. Sun et al 28 postulated that these mesenchymal stem cells were temporarily quiescent and could be reactivated under certain conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Autologous cancellous bone gra ment of many bone defects, accelerating fracture healing, and reducing complications (Giannotti et al, 2013b;Ismail et al, 2013;Ohgushi, 2014). According to the above mentioned "diamond concept", BM-MSCs provide the most appropriate cells for inducing bone repair, as they have a strong osteogenic potential and are easily obtained by culturing iliac crest aspirates (Akram et al, 2014;Gómez-Barrena et al, 2015).…”
Section: Bmac-acb Gramentioning
confidence: 99%